2007
DOI: 10.1590/s0102-311x2007001200028
|View full text |Cite
|
Sign up to set email alerts
|

Vítimas de acidentes de trânsito na faixa etária pediátrica atendidas em um hospital universitário: aspectos epidemiológicos e clínicos

Abstract: This study analyzes epidemiological and clinic characteristics of victims of traffic accidents. Data were obtained from medical records of children under 15 years of age (n = 1,123) admitted to a university hospital in Uberlândia, Minas Gerais State, Brazil, from 1999 to 2003. Mean age was eight years, 65.7% were boys, 76.6% were cyclists or pedestrians, 45.9% suffered head injuries, and 9% remained in hospital for more than two weeks. Fourteen (1.2%) died, 78.6% of these within 48 hours of hospitalization, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
8
0
8
Order By: Relevance
“…Among the vehicles specifi ed, there was a higher proportion of passenger vehicles, and the highest number of deaths occurred in pedestrians under 15 when compared to other RTA in this age group (64% in 2000 and 67% in 2005). In the city of Uberlândia, 46% of injured victims from zero to 14 years of age 25 were cyclists and 31% pedestrians. Among the most severely injured (admission to an intensive care unit), 81% were pedestrians and 7% cyclists.…”
Section: Pedestrians and Cyclistsmentioning
confidence: 99%
“…Among the vehicles specifi ed, there was a higher proportion of passenger vehicles, and the highest number of deaths occurred in pedestrians under 15 when compared to other RTA in this age group (64% in 2000 and 67% in 2005). In the city of Uberlândia, 46% of injured victims from zero to 14 years of age 25 were cyclists and 31% pedestrians. Among the most severely injured (admission to an intensive care unit), 81% were pedestrians and 7% cyclists.…”
Section: Pedestrians and Cyclistsmentioning
confidence: 99%
“…Deslandes and Silva [4] found that 69.3% of the victims of traffic accidents were male and the most affected age group was 20-39 years (60.5% in one hospital and 47.5% in the other). Freitas et al [7] noted the predominance of males (65.7%) of different ages (mean age 8 to 41 years) as victims of traffic accidents involving two vehicles and four wheels.…”
Section: Resultsmentioning
confidence: 99%
“…Baracat et al [1] also found that the upper and lower limbs were the most affected body parts, accounting for 40.7% of the accidents in the sample studied. Freitas et al [7] found that the upper and lower limbs accounted for 42% of the injured body part.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower number of deaths among bicycle occupants, whose vulnerability has been identified by descriptive studies 3,25 , may be explained by the fact that bicycles are still not a common means of local transportation, probably due to cultural issues and the city's hilly relief.…”
Section: Discussionmentioning
confidence: 99%